Kewajiban Menuntut Ilmu Mengembangkan Dan Mengamalkannya - Ika Ika; Asyifa Wasmin; Sastia Oktori; Siti Nurhalimah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Science is something very important in human life, Islam is very concerned about science, even at the beginning of the first verse that comes down is a verse about education, Islam is a perfect religion based on the Qur'an and hadith. Science is the key to the happiness of the world and the hereafter, if man wants to gain God's pleasure then man must worship to carry out His commandments and stay away from His prohibitions it must also use knowledge. Islam also commands people to study, develop and practice the knowledge they have gained for themselves and others.